Our oil and gas industry in the environment of COVID-19: opportunities for a sustainable industry - Bisetti Solari, Enrique (2021)
Peru is one of the pioneer countries in drilling for oil, especially in the north of the country in the 19th century. From that date to the present, there have been different important changes in the direction of the industry; such as the start of the production of Natural Gas Liquids (LGN) or the Camisea Project in Peru. At the beginning of this new century, we must take into account the technology that can increasingly develop different ways of exploiting gas and oil that are difficult to access, and thus expand the supply of the hydrocarbon industry worldwide. To all this, the importance of the changes that have been made due to the global health and economic crisis caused by COVID-19, will help us rebuild a modern, successful and sustainable industry.